Scheduling unit time arc shutdowns to maximize network flow over time: Complexity results. Issue 2 (8th October 2013) - Boland, Natashia; Kapoor, Reena; Kaur, Simranjit; Kalinowski, Thomas
Abstract We study the problem of scheduling maintenance on arcs of a capacitated network to maximize the total flow from a source node to a sink node over a set of time periods. Maintenance on an arc shuts down the arc for the duration of the period in which its maintenance is scheduled, making its capacity zero for that period. A set of arcs is designated to have maintenance during the planning period, which will require each to be shut down for exactly one time period. In general this problem is known to be NP‐hard. Here we identify a number of characteristics that are relevant for the complexity of instance classes. In particular, we discuss instances with restrictions on the set of arcs that have maintenance to be scheduled; series‐parallel networks; capacities that are balanced, in the sense that the total capacity of arcs entering a (nonterminal) node equals the total capacity of arcs leaving the node; and identical capacities on all arcs. © 2013 Wiley Periodicals, Inc. NETWORKS, Vol. 63(2), 196–202 2014